(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
In an increasingly complex and fast-paced construction industry, the gap between theoretical instruction and practical application remains a persistent challenge in engineering education. Many students struggle to fully grasp development planning processes ranging from initial site surveys to multidisciplinary technical drawings due to limited exposure to real-world practices. Addressing this issue, the present study evaluates the effectiveness of an academic–industry collaboration initiative, specifically an industrial talk, in enhancing students’ understanding of development planning within the construction context. Adopting a quantitative pre–post research design, the study collected 77 valid responses from participants comprising predominantly undergraduate engineering students, alongside lecturers and an industry speaker. A structured questionnaire measured self-reported understanding before and after the session, complemented by nine Likert-scale items assessing awareness, integration, and perceived benefits. Data were analysed using SPSS through descriptive statistics, reliability testing, paired samples t-tests, and group comparison analyses. The findings reveal a substantial and statistically significant improvement in participants’ understanding following the intervention. The mean score increased from 2.75 (pre-session) to 8.35 (post-session), with a highly significant t-test result (p < 0.001), indicating strong learning gains. The instrument demonstrated excellent reliability (Cronbach’s α = 0.965), confirming internal consistency. Importantly, no significant differences were observed across gender or participant groups, suggesting that the learning experience was inclusive and broadly effective. High satisfaction levels (mean = 4.68/5) further underscore the perceived value of the initiative. This study concludes that structured academic–industry engagements serve as powerful pedagogical tools in bridging the theory–practice divide in construction education. Beyond academic outcomes, such initiatives contribute to societal and environmental advancement by fostering industry-ready graduates equipped with practical competencies, collaborative skills, and a deeper appreciation of sustainable construction practices. By strengthening the alignment between education and industry needs, these efforts support the development of a more competent workforce capable of delivering efficient, well-coordinated, and environmentally responsible construction projects.